PENGABUH BERAT LABUR DAN KADAR PENGISI PEREKAT TANIN FORMALDEHIDA TERHADAP KETEGUHAN BEKAT LAPIS - adi santoso; rodjak memed; Paribotro sutigno (Jurnal Penelitian Hasil Hutan, 1991)
It has been known that  tannin formaldehyde  resin  is suitable for exterior plywood  adhesive. one   of the source of tannin is Acacia decurrens bark. A study on using tannin formaldehyde from.  Acacia  decurrens   bark has been done  to predict  the effect of  glue spread  and percentage of filler on the plywood   bonding strength. The results show that glue spread has not sigatficant effect on plywood  bonding strength, while percentage of  filler  has significant effect on plywood  bonding strength and all plywood resulted meet German  Standard requirement for  exterior purpose. (AW 100).From  the economic paint of view,  it is recommended. to use glue spread of 150 g/m2 and percentage of filler of 4o%.